Community college teacher preparation for diverse geographies : implications for access and equity for preparing a diverse teacher workforce - D'Amico, Mark M.; Lewis, Chance W. 1972- (Contemporary perspectives on access, equity, and achievement., 2019)
"Community colleges serve as the open door to higher education for marginalized, place bound, and/or financially challenged students and communities. One of the key ways marginalization occurs in diverse geographies is through several access limitations: access to affordable postsecondary education, access to curricula that lead to viable professions, access to diverse educational role models, and access to employment opportunities that can sustain communities. This underscores the importance of understanding "place" when addressing access and equity in higher education and the role of community colleges. The discussion of access and equity through the community college has implications for teacher education. Considering the documented importance of having a diverse teacher workforce in K-12 schools and the current mismatch between the diversity of students and the teachers in their schools, community colleges have a significant role to play. This book explores many topics related to the community college role in K-12 teacher education, including the community college mission, the policy landscape, partnerships, the transfer function, the community college baccalaureate, and others. Throughout the volume, the authors explore implications of access, equity, and geography and conclude with recommendations to guide future research and practice" --